Analisa Pengaruh Manajemen Material Terhadap Produktivitas Kerja Pada Proyek Konstruksi Gedung Bertingkat Di Kota Palangka Raya: Analysis Of The Effect Of Material Management On Work Productivity In Multi-Storey Building Construction Projects In Palangka Raya City. - Azzahra, Putri; Respati, Rida (Media Ilmiah Teknik Sipil, 2024)
Material management plays an important role in the process of implementing construction projects because materials are the largest cost component in the process. Material management is carried out to support timeliness, quantity accuracy, and cost accuracy. One way to achieve timeliness, quality, and cost is by implementing good work productivity. Productivity becomes a measure in considering whether a project is carried out effectively or not. This study aims to determine what factors in material management affect the productivity of construction project work. The method used in this research is quantitative. Data analysis using multiple linear regression tests with the help of the SPSS 23.0 application. The results of this study obtained a multiple linear regression equation Y = (3.684) + 0.025X1 + 0.043X2 - 0.039X3 - 0.013X5 + 0.031X7. Where the material management factors that affect project work productivity in this study are material procurement planning and scheduling, project organization and personnel, purchasing materials according to planning, storage and warehouse, and control and supervision.